WEB-BASED INFORMATION SYSTEM FOR THE RECAPITULATION OF THE ELECTION OF THE CHAIRMAN OF RW 011 PADANG SARAI PERMAI HOUSING - Setya Hadi, Harry; Gustina, Endang (Jurnal Manajemen Teknologi Informatika, 2024)
Recapitulation is an activity of summarizing data so that it becomes more useful in form, arrangement, nature or content with the help of hands or even equipment and following a series of formula steps, or a certain pattern. can facilitate the community in voting anywhere and anytime so that it can also save costs in the Election of RW Heads. making applications, analysis, namely gathering complete requirements, then analyzing and defining the requirements that must be met by the program to be built, design, namely producing an overall system and determining the flow of the software, implementation, namely where the entire design is converted into program codes, testing, namely merging the modules that have been made, verification, namely testing whether the system is in accordance with what has been approved, maintenance, namely the process of repairing the system according to what has been approved